Living on the edge: How to prepare for it? - Van Puyvelde, Martine; Gijbels, Daisy; Van Caelenberg, Thomas; Smith, Nathan; Bessone, Loredana; Buckle-Charlesworth, Susan; Pattyn, Nathalie (Frontiers in Neuroergonomics, 2022)
Isolated, confined, and extreme (ICE) environments such as found at Antarctic, Arctic, and other remote research stations are considered space-analogs to study the long duration isolation aspects of operational space mission conditions. We interviewed 24 sojourners that participated in different short/long duration missions in an Antarctic (Concordia, Halley VI, Rothera, Neumayer II) or non-Antarctic (e.g., MDRS, HI-SEAS) station or in polar treks, offering a unique insight based on first-hand information on the nature of demands by ICE-personnel at multiple levels of functioning. We explored how sojourners were trained, prepared, how they experienced the ICE-impact in function of varieties in environment, provided trainings, station-culture, and type of mission. A qualitative thematic analysis showed that the ICE-environment shapes the impact of organizational, interpersonal, and individual working- and living systems, thus influencing the ICE-sojourners’ functioning and that more specific training for operating in these settings would be beneficial. The identified pillars such as sensory deprivation, sleep, fatigue, group dynamics, displacement of negative emotions, gender-issues along with coping strategies such as positivity, salutogenic effects, job dedication and collectivistic thinking confirm previous literature. However, in this work, we applied a systemic perspective, assembling the multiple levels of functioning in ICE-environments. This approach could serve as a guide to develop future preparatory ICE-training programs, including all the involved parties of the crew system (e.g., family, on-ground crew) with attention for the impact of organization- and station-related subcultures and the risk of unawareness about the impact of poor sleep, fatigue, and isolation on operational safety that may occur on location.